Patients’ Perceptions of their Participation in a Clinical Trial for Postoperative Crohn’s Disease - ED Kennedy; JE Blair; R Ready; BG Wolff; AH Steinhart; PW Carryer; RS McLeod (Canadian Journal of Gastroenterology)
OBJECTIVE: To explore patients' perceptions of their participation in a randomized controlled trial.